2012
DOI: 10.1371/journal.pgen.1002784
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Plant-Associated Pseudomonas spp.: Insights into Diversity and Inheritance of Traits Involved in Multitrophic Interactions

Abstract: We provide here a comparative genome analysis of ten strains within the Pseudomonas fluorescens group including seven new genomic sequences. These strains exhibit a diverse spectrum of traits involved in biological control and other multitrophic interactions with plants, microbes, and insects. Multilocus sequence analysis placed the strains in three sub-clades, which was reinforced by high levels of synteny, size of core genomes, and relatedness of orthologous genes between strains withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
734
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(769 citation statements)
references
References 176 publications
(252 reference statements)
31
734
1
3
Order By: Relevance
“…The isolates S4LiBe and S5LiBe are very similar (99.8% 16SrRNA gene similarity) to each other and are very closely related (99.4 to 99.7%) to the P. protegens strains CHA0 T and Pf-5 [44]. However, a definite phylogenetic clarification would need further analysis based on concatenated alignments of several household genes [30,42], because 16S rRNA analysis alone cannot conclusively resolve very closely related species, like in the Pseudomonas fluorescens cluster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates S4LiBe and S5LiBe are very similar (99.8% 16SrRNA gene similarity) to each other and are very closely related (99.4 to 99.7%) to the P. protegens strains CHA0 T and Pf-5 [44]. However, a definite phylogenetic clarification would need further analysis based on concatenated alignments of several household genes [30,42], because 16S rRNA analysis alone cannot conclusively resolve very closely related species, like in the Pseudomonas fluorescens cluster.…”
Section: Discussionmentioning
confidence: 99%
“…have been broadly studied for their roles in plant growth promotion and biological control [16,17,21,25,30,46,59]. Plant growth promoting activities of Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…All these features make fluorescent pseudomonads interesting organisms for use as biofertilizers and biopesticides in sustainable agriculture and several products have been commercialized . On top of plant-beneficial activity, genomics has revealed unexpected and broader ecological versatility for these bacteria (Paulsen et al, 2005;Loper et al, 2012). Three of the best-characterized biocontrol strains, Pseudomonas protegens strains CHA0 and Pf-5 and Pseudomonas chlororaphis PCL1391, were shown to have potent insecticidal activity (Péchy-Tarr et al, 2008;Ruffner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A survey by Ruffner et al (2015) revealed that sub-clade 2 strains (Loper et al, 2012) neither harbor fit genes nor have ability to kill G. mellonella larvae. In contrast, all tested P. protegens and P. chlororaphis strains, which represent the sub-clade 1 (Loper et al, 2012), have both the toxin and injectable activity. Accordingly, Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…40). Although classified as P. fluorescens, recent comparative genomics studies indicate that they belong to at least three species 41 . Forty-eight communities were assembled from the eight genotypes, covering a richness of one (each of the eight genotypes in monoculture with two replicates each), two (16 combinations), four (12 combinations) and eight genotypes (4 replicates), according to a previously published design 19 .…”
Section: Methodsmentioning
confidence: 99%